1995
DOI: 10.1164/ajrccm.152.1.7599836
|View full text |Cite
|
Sign up to set email alerts
|

Purification of human lung leukotriene C4 synthase and preparation of a polyclonal antibody.

Abstract: Leukotriene (LT) C4 synthase is an integral membrane protein that catalyzes the conjugation of LTA4 to reduced glutathione to form LTC4. LTC4 synthase has been cloned and characterized from transformed cell lines, but the protein has not been defined from a tissue source. LTC4 synthase was purified to homogeneity from human lung tissue, utilizing S-hexyl glutathione chromatography followed by LTC4 affinity chromatography. A greater than 100,000-fold purification with a yield of 8 to 25% (n = 4) was achieved. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 19 publications
1
53
1
Order By: Relevance
“…2). The perinuclear region is a prominent location for enzymes of eicosanoid biosynthesis, either constitutively (48,49) or after translocation in response to calcium flux (4,50,51). Thus, group V sPLA 2 may act intracellularly, without a requirement for prior secretion, to amplify the effects of translocated cPLA 2 -␣.…”
Section: Figmentioning
confidence: 99%
“…2). The perinuclear region is a prominent location for enzymes of eicosanoid biosynthesis, either constitutively (48,49) or after translocation in response to calcium flux (4,50,51). Thus, group V sPLA 2 may act intracellularly, without a requirement for prior secretion, to amplify the effects of translocated cPLA 2 -␣.…”
Section: Figmentioning
confidence: 99%
“…Cytosolic phospholipase A 2 and 5-LO exist in the cytosol and translocate to the perinuclear membrane in response to calcium flux (29,30). 5-LO-activating protein and LTC 4 synthase are present at the perinuclear membrane in both resting and stimulated cells (31,32). Subsequent work implicated lipid bodies as a site of LT biosynthesis (26).…”
Section: Ltc4 Generationmentioning
confidence: 99%
“…Immunohistochemical analysis of human lung showed that LTC 4 synthase was localized to perinuclear membrane in alveolar macrophages [72]. Recently, it was reported that 5-lipoxygenase and LTC 4 synthase were assembled in lipid bodies in platelet activating factor (PAF) stimulated eosinophils [73], demonstrating cell variation in the localization of the enzymes involved in leukotriene synthesis.…”
Section: Cellular Formation Of Leukotrienesmentioning
confidence: 99%